2022
DOI: 10.1111/eos.12866
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of combining Krüppel‐like factor 4 score and grade of inflammation in a Norwegian cohort of oral tongue squamous cell carcinomas

Abstract: Krüppel‐like factor 4 (KLF4) is a zinc‐finger transcription factor involved in inflammation, cancer development, and progression. However, the relationship between KLF4, inflammation, and prognosis in oral cancer is not fully understood. KLF4 expression levels were examined in a multicenter cohort of 128 oral squamous cell carcinoma (OSCC) specimens from the tongue (OTSCC) using immunohistochemistry. In two external KLF4 mRNA datasets (The Cancer Genome Atlas/The Genotype‐Tissue Expression Portal), lower KLF4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Studies and evaluation of new therapies for premalignant epithelial lesions of the oral mucosa in humans appear suitable for this model (Nauta et al., 1997 ). According to this study and numerous other reports, 4‐NQO morphologically and histologically mimics human HNC lesions in the oral cavity (Hawkins et al., 1994 ; Søland et al., 2022 ). This model has a relative disadvantage in that tumours do not develop for long periods, and neoplastic transformations resist this model.…”
Section: Hnc In Rat Modelssupporting
confidence: 82%
“…Studies and evaluation of new therapies for premalignant epithelial lesions of the oral mucosa in humans appear suitable for this model (Nauta et al., 1997 ). According to this study and numerous other reports, 4‐NQO morphologically and histologically mimics human HNC lesions in the oral cavity (Hawkins et al., 1994 ; Søland et al., 2022 ). This model has a relative disadvantage in that tumours do not develop for long periods, and neoplastic transformations resist this model.…”
Section: Hnc In Rat Modelssupporting
confidence: 82%
“…Increased expression has been reported in human head and neck squamous cell carcinoma and is associated with poor prognosis and aggressiveness, corroborating its oncogenic role [ 64 , 65 ]. In contrast, Land et al [ 66 ] found an association between high KLF4 expression and a favourable prognosis. Another study reported the role of KLF4 in oral squamous cell carcinoma, in which mechanisms of action were described as both tumour suppressors and oncogenes [ 67 ].…”
Section: Discussionmentioning
confidence: 93%